Feasibility of Vaginal Hysterectomy for Female-to-Male Transgender Men. Issue 3 (March 2017) - Obedin-Maliver, Juno; Light, Alexis; de Haan, Gene; Jackson, Rebecca A.
Abstract : OBJECTIVE: To describe the hysterectomy data among a cohort of transgender men and nontransgender (ie, cisgender) women with a particular goal to evaluate the feasibility of vaginal hysterectomy among transgender men. METHODS: This cohort study includes all hysterectomies performed for benign indications on transgender men and cisgender women at a single academic county hospital from 2000 to 2012. Hysterectomy cases and patient gender were identified by billing records and confirmed by review of medical records. Primary study outcome was the hysterectomy route among transgender men compared with cisgender women. We also examined risk factors and operative outcomes. Student two-sided t tests, χ 2 analysis, and descriptive statistics are presented; sensitivity analyses using regression techniques were performed. RESULTS: Hysterectomies for benign gynecologic procedures were performed in 883 people: 33 on transgender men and 850 on cisgender women. Transgender men were younger, had fewer pregnancies and deliveries, and smaller uteri. The leading indication for hysterectomy differed significantly: pain (85%) was most common among transgender men (compared with 22% in cisgender women; P <.001), whereas leiomyomas (64%) was most common for cisgender women (compared with 21% in transgender men; P <.001). Vaginal hysterectomies were performed in 24% transgender men and 42% of cisgender women. Estimated blood loss was less among transgender men ( P =.002), but when uterine size and route of hysterectomy were considered, the difference between gender groups was no longer significant. There was no difference in patients experiencing complications between the groups. CONCLUSION: Transgender men and cisgender women have different preoperative characteristics and surgical indications. Vaginal hysterectomies have been successfully completed among transgender men. Because vaginal hysterectomy is a viable procedure for this population, it should be considered in surgical planning for transgender men. Abstract : Supplemental Digital Content is Available in the Text.For transgender men who are undergoing hysterectomy, the vaginal route is a viable option.